Negoscalpic Properties of Cutting Object - Barakaev Nusratilla Rajabovich; Amonov Mahmud Idris ugli; Sohibov Ibodullo Adizmurodovich (Research Parks Publishers, 2021)
The article covers the properties of capillary-porous multiphase food half-finished products processed by the method of sliding cutting, as well as research of cutting objects using various rheological models.